Analisis Ketersediaan Air DAS Sausu Untuk Kebutuhan Air Pada D.I. Sausu Bawah, Kabupaten Parigi Moutong - Andita, W.; Lipu, S. (Civil Engineering Department, Tadulako University, 2020)
This study aims to grasp and analyze the water availability in Sausu Watershed and the need of water in Lower Sausu Irrigation Scheme. The research begins with data collection and hydro-climatological analysis to determine whether the water is enough or not enough to be used during a hydrological period. To obtain the comparison between the needs and availability of water, a hydro-climatological analysis and calculation of water need are carried out. Methods that used namely the Penman Modification method and the F.J Mock method. Penman modification method is used to calculate monthly evapotranspiration (ETo) by taking into account climatological factors such as air temperature, wind speed, solar radiation and relative humidity. By applying the F.J.Mock method for calculating the water availability, the amount of water flow from the rain, characteristics of the drainage area and evapotranspiration can be calculated. Based on the results of data analysis for Sausu watershed area of 568.64 km², it shows that the average value of water availability in the lower intake for 1 year is app. 30.19 m³/sec with the maximum value of app. 48.149 m3/sec and the minimum is app. 4.134 m3/sec. Whereas the maximum water demand in the Lower Sausu irrigation scheme is app. 1.77 m³/sec with the minimum of 0.04 m3 /sec and the average is app. 0.49 m3/sec. It can be concluded that the water availability in the Sausu River Basin is sufficient to meet the water needs of the Lower Sausu Irrigation Scheme throughout the year, or there is a continuous surplus.